HUBUNGAN MANAJEMEN LABA SEBELUM IPO TERHADAP RETURN SAHAM DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Surya, Angga; Januarti, Indira (Diponegoro Journal of Accounting, 2012)
The financial statements is a source of information for investors in making investment decisions. At the time of IPO, managers tend to take advantage of high information asymmetry for earning management in order to attract investor in earnings report. The purpose of this study is to investigate earnings management during periods around the Initial Public Offering of a company. This study also examine the effect of earnings management on stock returns and examine firm size in moderating the relationship between earning management and stock return. Sample of the study consists 68 non-financial companies that take place IPO during 2005-2010. Research model to examine the discretionary accruals using the Modified Jones models. One test sample t-test is used to test whether significant discretionary accrual among IPOs and multiple linear analysis is used to examine the effect of earnings management to market reaction and the moderating influence of firm size in relation to the stock returns of earnings management. The results shows that there are patterns of earnings management in t-1, t0 and t +1 periods. 1 year of earnings management before the IPO do not significantly influence stock returns. However, the company size proved to moderate the relationship of earnings management 1 year before the IPO shares to return with positive coefficient.